Integritas Kepemimpinan Antikorupsi di Sektor Kesehatan - Ayunigtyas, Dumilah; Parinduri, Siti Khodijah; Susanti, Fitria Aryani (Komisi Pemberantasan Korupsi, 2018)
Health is very strategic and plays an important role in determining the welfare of the Indonesian population. The budget for health in the 2017 Revenue and Expenditure Budget (APBN) of Rp 104 trillion, even increased Rp 500 billion from the draft RAPBN 2017. The amount of budget in the health sector opens opportunities abused by relevant agencies and individuals. This study aims to analyze the concept and implementation of anticorruption leadership integrity in the health sector. The research is conducted with a qualitative approach to explore the views of stakeholders in the health sector and establish the thematic phenomena of content analysis of the interview results. The research finds similar concerns about the incidence of corruption in the health sector as well as other sectors, hence it becomes highly relevant to prepare leaders with the anticorruption leadership competence in the health sector. Reference rules for employee recruitment, appraisal and placement of health sector structural officials have not explicitly stated anti-corruption competence as part of the requirements that must be owned. The concept of anticorruption leadership stems from the value of usefulness, willingness to help, and